2002
DOI: 10.1159/000066766
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Absolute Oral Bioavailability of an 800-mg Oral Dose of Telithromycin in Healthy Young and Elderly Volunteers

Abstract: Background: This two-way, randomized, single-dose, crossover study determined the pharmacokinetics and absolute oral bioavailability of telithromycin in young and elderly healthy subjects. Methods: Twelve young (18–40 years) and 12 elderly (>65 years and ≤85 years) subjects received a single 800-mg oral dose of telithromycin or an intravenous infusion of 400 mg (young subjects) or 480 mg (elderly subjects) of telithromycin over 2.5 h in two treatment periods, separated by a 1-week washout period. The plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 4 publications
3
27
0
Order By: Relevance
“…Following a single 800-mg dose, the AUC 0-G determined in plasma was 10.83 mg ؒ h/l (7.03-14.64) [18]. These data corroborate the higher drug exposures seen once steady state is achieved, as is the case in our current study.…”
Section: Discussionsupporting
confidence: 90%
“…Following a single 800-mg dose, the AUC 0-G determined in plasma was 10.83 mg ؒ h/l (7.03-14.64) [18]. These data corroborate the higher drug exposures seen once steady state is achieved, as is the case in our current study.…”
Section: Discussionsupporting
confidence: 90%
“…Telithromycin has potent activities both in vitro and in vivo against common respiratory tract pathogens (2), and its spectrum of activity also extends to atypical and intracellular pathogens (3). The clearance, the volume of distribution, the half-life, the plasma protein binding, the urinary excretion, and the extent of absolute oral bioavailability (F) of telithromycin in humans are 12-16 ml/min/kg, 2.1-4.5 l/kg, 7-23 h, 70%, 19-27% of the dose, and 41-112%, respectively (4)(5)(6). Recently, Lee and Lee (7) reported that telithromycin is primarily metabolized via hepatic microsomal cytochrome P450 (CYP) 3A1/2 in male Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of telithromycin is approximately 60%, and absorption appears to be rapid, reaching C max (maximum concentration) of 1.9 mg/L in 1 hour [19]. Cethromycin appears to have a dose-dependent absorption with time to C max (t max ) increasing from 0.9 to 5.1 hours with increasing dosage [3••, 19,20].…”
Section: Absorptionmentioning
confidence: 99%